The Effectiveness Of Vernonia Amygdalina (African Bitter Leaf) Tea For Reducing Cholesterol Levels In Individuals With Hypercholesterolemia - Nunik Purwanti; Rahmadiar Aditya (Jurnal Ilmiah Kesehatan, 2021)
Advances in technology and high activities at work cause a person to prefer fast food, increasing the risks of high cholesterol levels. Meanwhile, the healing of hypercholesterolemia requires a long treatment time. One of them is non-pharmacological treatment using Vernonia amygdalina (African bitter leaf) tea. This study analyzes V.amygdalina (African bitter leaf) effectiveness for reducing the cholesterol levels in individuals with hypercholesterolemia. The design of this study was a quasi-experimental design, with a non-equivalent control group design. The population involved individuals with hypercholesterolemia in the village of Kedensari RW 05 Tanggulangin, Sidoarjo. There were 40 respondents in this study using the purposive sampling technique – 20 respondents in the experimental group and 20 respondents in the control group. The independent variable was V.amygdalina tea, whereas the dependent variable was cholesterol levels. The data were analyzed using the Wilcoxon and Mann-Whitney tests. The p-value of the Wilcoxon test and Mann-Whitney signed-ranks test was (0.000)<α(0.005), which illustrated that V.amygdalina (African bitter leaf) tea was useful for the treatment of hypercholesterolemia. In conclusion, tea made from African bitter leaf affects in reducing cholesterol levels. Therefore, this paper recommends using V.Amygdalina in other management forms besides tea because of its rich benefits as an alternative non-pharmacological hypercholesterolemia treatment.